Uptake of Polymyxin B into Renal Cells - Abdelraouf, Kamilia (American Society for Microbiology, 2014)
Polymyxin B is increasingly used as a treatment of last resort against multidrug-resistant Gram-negative infections. Using a mammalian kidney cell line, we demonstrated that polymyxin B uptake into proximal tubular epithelial cells was saturable and occurred primarily through the apical membrane, suggesting the involvement of transporters in the renal uptake of polymyxin B. Megalin might play a role in the uptake and accumulation of polymyxin B into renal cells.